Ethnoveterinary survey of trypanocidal medicinal plants of the beninese pharmacopoeia in the management of bovine trypanosomosis in North Benin (West Africa) - Christophe Iwaka; Erick Virgile Bertrand Azando; Thierry Dehouegnon Houehanou; Sabi Kora; Yaya Idrissou; Pascal Abiodoun Olounlade; Sylvie Mawulé Hounzangbe-Adote (Heliyon, 2023)
Cattle breeding is of great socio-economic importance for Benin's cattle farmers in general and those of North Benin in particular. The objective of this study is to inventory the natural products of medicinal plants of the Beninese pharmacopoeia for the management of trypanosomes in cattle in North Benin. The methodology consisted of individual and semi-structured interviews with cattle farmers on the use of medicinal plants. A total of 360 cattle farmers were selected and interviewed in twelve villages in four municipalities (Tchaourou, N'dali, Bembèrèkè and Gogounou) in northern Benin. Different quantitative ethnobotanical indices were calculated to determine the level of use of plant species. The Relative Frequency of Citation (RFC), the Informant Consensus Factor (ICF = 0.918) and the Generic Coefficient (Rg = 1.04) were evaluated. The knowledge of medicinal plants was influenced by the level of education and the main activity of those who practiced animal husbandry. The results yielded 48 medicinal plants for veterinary use belonging to 46 genera and 28 families. The Leguminosae family (12.50%) was the most represented. The most cited plants with a RFC above 10% were K. senegalensis, P. africana, K. africana, M. inermis, S. latifolius, M. polyandra. The parts used were leaves (46.15%); barks (24.62%) and roots (15.38%). Decoction (53.23%), plundering (32.26%) and maceration (11.26%) were the main methods of preparation. The administration was mainly by oral route. The calculated indices show a high diversity of medicinal plants with trypanocidal properties in the control of cattle trypanosomosis in the Sudanese and Sudano-Guinean zones of northern Benin. Plant species with high citation and RFC values should be selected for comprehensive pharmacological and phytochemical research to validate this ethnomedical knowledge in the management of cattle trypanosomosis.